2014
DOI: 10.1002/2013ja019491
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric and ionospheric response to sudden stratospheric warming of January 2013

Abstract: In this work, we examine the atmospheric and ionospheric responses to the January 2013 sudden stratospheric warming (SSW) event. To examine the atmospheric and ionospheric behavior during this event, three main parameters are used (1) Total Electron Content (TEC) collected from the International Global Positioning System and from the Brazilian Network of Continuous Monitoring stations, (2) daytime E × B vertical drift derived from the magnetometers located at the equatorial station Alta Floresta (9.9°S, 55.9°W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 21 publications
5
55
0
Order By: Relevance
“…This behavior is observed in the equatorial vertical plasma drift [ Chau et al , , ; Anderson and Araujo‐Pradere , ; Fejer et al , , ; Rodrigues et al , ], as well as low‐latitude ionosphere electron densities and total electron content (TEC) [ Goncharenko et al , , , ; Pedatella and Forbes , ; Yue et al , ; Lin et al , ; Pancheva and Mukhtarov , ]. Similar local time variations occur in the equatorial vertical plasma drift and electron density [e.g., Jonah et al , ], providing evidence that the electron density variability is driven by changes in the equatorial electrodynamics. Numerical modeling studies have further revealed that changes in the lunar and/or solar semidiurnal migrating tides are the primary driver of the electrodynamic changes during SSWs [ Fang et al , ; Jin et al , ; Pedatella et al , ; Pedatella and Liu , ; Wang et al , ].…”
Section: Introductionmentioning
confidence: 77%
“…This behavior is observed in the equatorial vertical plasma drift [ Chau et al , , ; Anderson and Araujo‐Pradere , ; Fejer et al , , ; Rodrigues et al , ], as well as low‐latitude ionosphere electron densities and total electron content (TEC) [ Goncharenko et al , , , ; Pedatella and Forbes , ; Yue et al , ; Lin et al , ; Pancheva and Mukhtarov , ]. Similar local time variations occur in the equatorial vertical plasma drift and electron density [e.g., Jonah et al , ], providing evidence that the electron density variability is driven by changes in the equatorial electrodynamics. Numerical modeling studies have further revealed that changes in the lunar and/or solar semidiurnal migrating tides are the primary driver of the electrodynamic changes during SSWs [ Fang et al , ; Jin et al , ; Pedatella et al , ; Pedatella and Liu , ; Wang et al , ].…”
Section: Introductionmentioning
confidence: 77%
“…Associated with the SSW is the shift of the daytime maximum vertical drift from prenoon to the afternoon [e.g., Chau et al , ; Goncharenko et al , , ; Fejer et al , ; Anderson and Araujo‐Pradere , ; Jonah et al , ] over several days which happens during the enhanced drift phase and can be reproduced by numerical models using only solar tidal forcing if SW 2 has the right phase shift [e.g., Fuller‐Rowell et al , ; Jin et al , ; Maute et al , ]. However, the modulation of the vertical drift examined in the present study can only be reproduced by including solar and lunar tidal forcing.…”
Section: Discussionmentioning
confidence: 99%
“…Observed disturbances in the thermosphere [e.g., Forbes and Zhang , ; Liu et al , , ] and ionosphere [e.g., Chau et al , ; Stening , ; Jonah et al , ; Pancheva et al , ; Yamazaki , ] could be attributed to SSW events. Numerical models were employed to investigate the vertical coupling between the lower and upper atmosphere [e.g., Fuller‐Rowell et al , ; Fang et al , ; Pedatella et al , ; Jin et al , ; Maute et al , , ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar behavior was observed at the 60° magnetic longitude sector over Brazil by Jonah et al . []. In that study the daytime vertical plasma drift was inferred from a pair of magnetometers, one located under the magnetic equator and another at an off‐equatorial position.…”
Section: Introductionmentioning
confidence: 99%